SISTEM PENDUKUNG KEPUTUSAN (SPK)MENGGUNAKAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNUE (SMART) DALAM MENENTUKAN JENIS PELANGGARAN DAN SANKSI DI MADRASAH ALIYAH NURUL JADID (MANJ) - Jovi Irawan; M. Syafiih (INFOTECH journal, 2024)
This research aims to develop a web-based application system using the simple multi attribute rating technique (SMART) method to determine sanctions for violations by Madrasah Aliyah Nurul Jadid (MANJ) students at the Nurul Jadid Paiton Islamic Boarding School, Probolinggo. The need for this system is based on the importance of efficiency and accuracy in determining types of violations and sanctions for students based on their violations while studying at Madrasah Aliyah Nurul Jadid (MANJ). This research method involves analyzing data from 100 students who had problems while attending school. . Data is processed using the simple multi attribute rating technology (SMART) method to determine student violation sanctions into Violation categories: The results of these provisions will provide objective and accurate guidance in determining the type of violation and student sanctions that are in accordance with the policies that have been established. by the Madrasah Aliyah Nurul Jadid (MANJ) institution. The results of the research show that using the simple multi attribute rating technology (SMART) method is quite effective in managing student violations, thereby increasing the efficiency and accuracy of the student coaching process. The implementation of web-based technology makes it easier to access and use the system by administrators and the Madrasah Discipline section. Aliyah Nurul Jadid (MANJ), to ensure that the process of managing violations and coaching students becomes faster, more accurate and more objective. Overall, this research succeeded in developing a responsive and efficient decision support system, which not only solved specific problems at Madrasah Aliyah Nurul Jadid (MANJ) but also made a significant contribution to the development of similar systems in other Islamic educational institutions.